Effectiveness of Using Virtual Laboratories in Improving The Quality of Science Learning in Schools With Limited Facilities - Nabila Khaerunnisa; Sri Aliyah; Silviatul Wardiana; Gunawan Gunawan; Nina Nisrina (Indonesian, 2025)
This study aims to examine the effectiveness of virtual laboratories in improving the quality of science learning in schools with limited facilities, particularly in disadvantaged areas in Indonesia known as 3T regions (frontier, outermost, and underdeveloped areas), which refer to remote Indonesian areas with limited access to educational facilities. These regions generally face significant challenges in accessing adequate educational infrastructure, including laboratory facilities. This study employs a qualitative approach using a literature review method on relevant scientific articles published between 2015 and 2024. The literature sources were obtained from various academic databases such as Google Scholar, Publish or Perish, and other scientific journals. From the initial search results, a number of articles were identified and then screened based on inclusion criteria such as relevance to the research topic and publication year, resulting in ten key articles selected for in-depth analysis. The results show that virtual laboratories can serve as an effective alternative to support science learning, particularly in visualizing abstract concepts and facilitating students’ understanding of scientific processes. Therefore, the integration of virtual laboratories is highly recommended to improve the quality of science learning in schools with limited facilities.